Performance of contrast-enhanced ultrasound for lymph node metastasis in papillary thyroid carcinoma: a meta-analysis - Yong Yu; Lin-Lin Shi; Hua-Wei Zhang; Qian Wang (Endocrine Connections, 2023)
Background: Papillary thyroid carcinoma is the most common thyroid carcinoma worldwide. Papillary thyroid carcinoma metastasis to the cervical region increases the probability of local or regional recurrence and the requirement for further surgery. Contrast-enhanced ultrasound has been suggested as a possible adjunct diagnostic technique for evaluating papillary thyroid carcinoma metastatic lymph nodes in several studies. This meta-analysis aims to evaluate the diagnostic accuracy of contrast-enhanced ultrasound for cervical lymph nodes metastatic in papillary thyroid carcinoma patients. Methods: A search for studies evaluating the role of contrast-enhanced ultrasound for assessing cervical lymph nodes metastatic in papillary thyroid carcinoma patients from January 2000 to May 2022 was performed in PubMed, Embase, OVID, and Web of Science databases. The Quality Assessment of Diagnostic Accuracy Studies 2 evaluated the quality of the studies. All analyses were performed using Review Manager 5.3 and Stata 17.0. Results: A total of seven articles were finally included in this study. Perfusion type, enhancement homogeneous, hilum absent, and perfusion defect were involved in the meta-analysis as the standard of contrast-enhanced ultrasound, among which, perfusion type showed the best diagnostic performance. The pooled estimated sensitivity, specificity, positive likelihood, negative likelihood ratio, and diagnostic odds ratio of perfusion type in contrast-enhanced ultrasound for detecting lymph node metastasis were 0.95 (0.91, 0.97), 0.87 (0.69, 0.96), 7.51 (2.80, 20.14), 0.06 (0.03, 0.10), and 124.17 (42.78, 360.46), respectively. Heterogeneity was moderate. Conclusion: The perfusion type in contrast-enhanced ultrasound has good diagnostic performance for cervical lymph nodes metastasis in papillary thyroid carcinoma patients.